2014
DOI: 10.1155/2014/167193
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Partial Blockage Effect on Film Cooling Effectiveness

Abstract: Three-dimensional numerical calculation was performed to investigate the effects of partial blockage inside cylindrical film holes on the film cooling effectiveness over a flat plate. Five blockage ratios ranged from 0.1 to 0.5 and a series of blockage positions were considered under the blowing ratios of 0.3–1.5. It is found that the blockage position has a significant influence on mainstream-coolant jet interaction. The partial blockage located at the leading edge of coolant-hole exit mitigates the primary v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Cheng et al [25] conducted a numerical investigation of the effects that deposition location and blowing ratio have on film cooling effectiveness using Fluent.…”
Section: 31: Deposit Effect On Film Coolingmentioning
confidence: 99%
“…Cheng et al [25] conducted a numerical investigation of the effects that deposition location and blowing ratio have on film cooling effectiveness using Fluent.…”
Section: 31: Deposit Effect On Film Coolingmentioning
confidence: 99%
“…Somawardhana et al [12] investigated the effect of geometric parameters on the cooling efficiency and found that the deposition shape had little effect on the cooling efficiency, but the deposition height had a great impact on the cooling efficiency. For the internal hole blockage, Pan et al [13] studied the effect of particle blockage in the monoclinic hole on film cooling, and analyzed the influence of different positions of the blockage in the hole on film cooling. The results showed that the blockage can severely affect the film cooling when it was on the upstream surface of the hole's inner wall.…”
Section: Introductionmentioning
confidence: 99%
“…The reasons causing the decrease or increase were analyzed through instantaneous flow field captured by Jovanovic et al [13]. Cheng et al [14] conducted a numerical investigation on hole-blockage. They found that the location of the blockage has much influence in the cooling effectiveness.…”
Section: Introductionmentioning
confidence: 99%